2016
DOI: 10.3171/2015.2.jns142771
|View full text |Cite
|
Sign up to set email alerts
|

Causes of 30-day readmission after aneurysmal subarachnoid hemorrhage

Abstract: OBJECTIVE Hospital readmission is a common but controversial quality measure increasingly used to influence hospital compensation in the US. The objective of this study was to evaluate the causes for 30-day hospital readmission following aneurysmal subarachnoid hemorrhage (SAH) to determine the appropriateness of this performance metric and to identify potential avenues for improved patient care. METHODS The authors retrospectively reviewed the medical records of all patients who received surgical or endovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 31 publications
0
40
2
Order By: Relevance
“…3,4,14,15,25 In addition, it is the most common cause of readmission after aSAH. 13 CSF shunting is prone to short-and long-term complications, including life-threatening obstructions and infections. 15 Studies have found that shunting after aSAH related to acute hydrocephalus, 2 Figure).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,14,15,25 In addition, it is the most common cause of readmission after aSAH. 13 CSF shunting is prone to short-and long-term complications, including life-threatening obstructions and infections. 15 Studies have found that shunting after aSAH related to acute hydrocephalus, 2 Figure).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Therefore, it is important to identify and understand the factors that increase risk for shunting and to eliminate or mitigate the reversible factors that put aSAH patients at risk. Also, recognition of predictive variables and identifying patients at risk for shunt-dependent hydrocephalus (SDHCP) could lead to optimized management with avoidance of increased neurological morbidity, impaired functional outcome and quality of life, and extended hospital stays associated with chronic hydrocephalus.…”
mentioning
confidence: 99%
“…Because of the complexity of assessing preventability, we used a consensus review process similar to that used in other readmission-preventability studies. 13,20,21 Each case had 1 primary reviewer, with no fewer than 3 pediatricians participating in the consensus review. In circumstances in which the readmission involved significant subspecialty care (eg, congenital heart disease postoperative management), relevant subspecialists were consulted.…”
Section: Data Collectionmentioning
confidence: 99%
“…Patients can suffer from electrolyte abnormalities, 2-5 delayed cerebral ischaemia (DCI), 6-8 further bleeding 9,10 and infection. 11,12 These complications are not uncommon, and have been associated with a worse clinical outcome. 13 Once admitted into NCCU, there is no set time period for how long SAH patients should remain for monitoring.…”
Section: Introductionmentioning
confidence: 99%